97.8k views
2 votes
Find x step by step (10 points)

Find x step by step (10 points)-example-1
User ESV
by
4.6k points

2 Answers

7 votes

Answer:


\boxed{\left \{ {{√((n-m)(m+n))} \atop {-√((n-m)(m+n))}} \right.}

Solution Steps:

- Steps using the quadratic formula -

______________________________

1.) Subtract n² from both sides:


  • n^2-n^2=0

  • m^2-n^2=m^2-n^2

2.) Rewrite:

This equation is in standard form: ax² + bx² + c = 0. Substitute 1 for a, 0 for b, and (m-n) (m+n) for c in the quadratic formula,
\frac{-b\frac{+}{}√(b^2-4ac) }{2a}:


  • x^2+m^2-n^2=0

2.a) Turns into:


  • x=\frac{0\frac{+}{}√(0^2-4(m-n)(m+n))}{2}

3.) Square 0:


  • 0^2=0 (Also means it Cancels out.)

4.) Take the square root of −4(m−n)(m+n):

This just means combine them by squaring.


  • -4^2=2 (Half it, don't square it.)

  • (m-n)(m+n)^2=(n^2-m^2)

4a.) Our equation should look like this now:


  • x=\frac{0\frac{+}{}2√((n^2-m^2))}{2}

5.) Solve the equation using ±:

Solve the equation
x=\frac{0\frac{+}{}2√((n^2-m^2))}{2}:

5a.) Solve the equation when ± is plus:


  • x=√((n-m)(m+n))

5b.) Solve the equation when ± is minus:


  • x=-√((n-m)(m+n))

______________________________

Hope this helps!

If you have any questions, or need help with anything else, feel free to ask! I'm happy to help!

- TotallyNotTrillex -

User Humberto Pinheiro
by
5.6k points
6 votes

Answer:


√((n-m)(n+m)) &
-√((n-m)(n+m))

Explanation:

1) Subtract
m^(2) from both sides. This should leave you with
x^(2)=n^(2)-m^(2).

2) Square root both sides. This should leave you with
x=√(n^2-m^2) &
x=-√(n^2-m^2).

You can stop here if this is what the problem is asking for. However, it is not fully simplified.

3) Factor the equation. This should leave you with
√((n-m)(n+m)) &
-√((n-m)(n+m)).

User Sakabako
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.